2012
DOI: 10.1380/ejssnt.2012.29
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermal Synthesis of Nitrogen-Containing Graphene for Electrochemical Oxygen Reduction in Acid Media

Abstract: Graphene is ideally suited to electrochemistry by virtue of its high surface area and impressive electronic properties. Nitrogen incorporation can be used to tailor the properties of graphene. Here we present a simple solvothermal technique to produce a nitrogen-containing foam-like macroporous graphene powder doped with up to 15 wt% nitrogen. This is applied as an effective non-precious, metal-free electrochemical catalyst for oxygen reduction in acid media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Non‐PGM electrocatalysts are often variations on N‐coordinated Fe or Co in a carbon matrix (i.e., Fe/N/C, Co/N/C), or simply metal‐free N‐doped carbon . N‐doped carbon nanotube powders, nanotube arrays, graphene, nanocages, and carbon nitrides have been studied in recent years for reactions including: (i) the ORR, (ii) photocatalytic water splitting, and (iii) photocatalytic CO 2 reduction. In (iii), the primary products include CO, methanol, and ethanol, but at low quantum yield .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non‐PGM electrocatalysts are often variations on N‐coordinated Fe or Co in a carbon matrix (i.e., Fe/N/C, Co/N/C), or simply metal‐free N‐doped carbon . N‐doped carbon nanotube powders, nanotube arrays, graphene, nanocages, and carbon nitrides have been studied in recent years for reactions including: (i) the ORR, (ii) photocatalytic water splitting, and (iii) photocatalytic CO 2 reduction. In (iii), the primary products include CO, methanol, and ethanol, but at low quantum yield .…”
Section: Introductionmentioning
confidence: 99%
“…In (iii), the primary products include CO, methanol, and ethanol, but at low quantum yield . We have previously demonstrated that carbon nitride (g‐C 3 N 4 ) exhibits ORR activity, especially when synthesized on a conductive support with large surface area . High temperature treatment played a critical role in the catalytic activity, with optimal activity achieved after pyrolysis at 1000 °C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, solvothermal chemistry has been employed for synthesizing graphene, which has made it possible to produce large quantities with varying quality. [8][9][10] Polymer electrolyte membrane fuel cells (PEFCs) are clean and environmentally friendly power sources for stationary, portable, and vehicular applications. They display rapid response times, high power densities and are extremely energy efficient.…”
mentioning
confidence: 99%
“…To avoid the presence of transition metals, our group began synthesis of nitrogen-doped graphene foam via thermal decomposition of sodium alkoxides and subsequent heat-treatment. 30,31 Due to the high surface area and unique structure of these electrocatalysts, the ORR currents achieved were much higher than those previously obtained. Due to the purity of the precursors, and the synthesis in Teflon vessels, such samples are proven to be free of metal contamination.…”
mentioning
confidence: 76%